(untitled) (IAHS Medical Journal, 2023)
Background: The timing of cholecystectomy for acute cholecystitis has been debated with most studies favoring early cholecystectomy. However, most surgeons in Bangladesh prefer to delay surgery in the acute phase. The study aimed to compare between early Laparoscopic Cholecystectomy (LC) with that of delayed laparoscopic cholecystectomy in the management of acute calculus cholecystitis. Materials and methods: This quasi-experimental study included a total of 74 patients with a diagnosis of acute calculous cholecystitis as per Tokyo guideline from the Surgery Department, Chittagong Medical College Hospital, during August 2019 to July 2020. Thirty-seven patients underwent early cholecystectomy (Within 7 days of onset of symptoms) and 37 patients underwent elective or delayed cholecystectomy (After a gap of 6-8 weeks from the acute attack). Peroperative events, postoperative complications, length of hospital stay and days needed to return to full activity were compared between two groups. Results: Both early and delayed groups were similar in-terms of their baseline demographic and clinical characteristics. Significantly higher number of patients in the early group had difficult Callot’s triangle dissection (59.4% vs. 27.1%, p<0.01) and lower number of patients had difficult gallbladder bed dissection (5.4% vs. 37.8%, p<0.001) than the delayed group. The proportion of the patients required conversion to open surgery was 10.8% and 6.1%, respectively in early and delayed group (p=0.691). Total hospital stay was shorter in the early surgery group than the delayed surgery group (6.05±0.52 vs. 12.03±1.46 days, p=0.001). Wound infection, duration of hospital stays following surgery, and days need to return to full activity after surgery was similar between two groups. Conclusion: Early cholecystectomy is feasible and safe for acute cholecystitis and is better method of treatment because of its shorter hospital stay, which is a major economic benefit to both the patient and health care system. IAHS Medical Journal Vol 5(2), Dec 2022; 11-14